Assessment and Remediation of Soils Contaminated by Potentially Toxic Elements (PTE) - Spagnuolo, Matteo; Adamo, Paola; Garau, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Many soils worldwide are contaminated with potentially toxic elements (PTEs). These elements can be taken up by plant roots and accumulate in plants' organs, thus becoming a danger for the health of humans and animals. Therefore, it is still essential and urgent to understand the behavior of such contaminants in soil and find sustainable approaches to reduce the risk posed by their presence in soil systems. This volume contains ten original research articles. Four articles deal with the assessment of bioavailability of PTEs in contaminated soils, three articles report results on the application of phytoremediation to PTEs contaminated soils, one paper is related to the source-sink relationships of PTEs at basin scale, and two manuscripts address the issue of PTE contamination in urban soils.